2017
DOI: 10.12965/jer.1732848.424
|View full text |Cite
|
Sign up to set email alerts
|

Influence of expectations plus mobilization with movement in patient with lateral epicondylalgia: a pilot randomized controlled trial

Abstract: The aim of this study was to determine the influence of expectations plus mobilization with movement (MWM) in kinesiophobia, perceived disability and sensorimotor variables in patients with lateral epicondylalgia. A pilot randomized controlled trial in 24 patients with lateral epicondylalgia was conducted. Perceived pain, pain-free grip strength, pressure pain detection threshold, kinesiophobia measured with the short version of Tampa Scale of Kinesiophobia, perceived disability of the upper limb measured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…Despite recognition that patient expectations has a role in influencing functional outcomes and the decision to pursue surgical care in patients with RCRSP [8-10], there have been few studies designed to test interventions designed to change expectations [15,16]. Research has shown that the best predictor of functional outcomes with a conservative approach are pre-treatment, patient expectations [15,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recognition that patient expectations has a role in influencing functional outcomes and the decision to pursue surgical care in patients with RCRSP [8-10], there have been few studies designed to test interventions designed to change expectations [15,16]. Research has shown that the best predictor of functional outcomes with a conservative approach are pre-treatment, patient expectations [15,61].…”
Section: Discussionmentioning
confidence: 99%
“…Patient expectations are beliefs or attitudes that include pre-treatment thoughts and beliefs regarding the need for specific treatment methods and the timing and intensity of these methods. Brief interventions designed to alter and enhance treatment expectations for conservative treatment appear to result in slight improvements in expectations [15,16], but not outcomes. The few interventions that have been tested have methodological problems including the failure to attend to issues of treatment fidelity and reliance on overly simplistic methods for altering expectations such as a patient handout or a one-time educational program [15,16].…”
Section: Introductionmentioning
confidence: 94%
“…Thirty-one studies were included in the final analysis (Beltran-Alacreu et al, 2015 ; Hidalgo et al, 2015 ; Pires et al, 2015 ; Sarig Bahat et al, 2015 ; Castro-Sánchez et al, 2016 ; Pillastrini et al, 2016 ; Cruz-Díaz et al, 2017 ; Martínez-Cervera et al, 2017 ; Yilmaz Yelvar et al, 2017 ; Birinci et al, 2019 ; Gholami et al, 2020 ). The identification process is shown by a flow diagram in Figure 1 (Moher et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with lateral epicondylitis experience decreased grip strength as a result of pain. Grip strength is associated with decrease in bone density in women and may be used to predict early death rates, onset of a disability, post-operative complications, and decreased cognitive ability in elderly people 14 ) . This study examined the effects of active concentric contraction of the wrist flexors and extensors according to the utilized stimulation frequency of TENS on pain and grip strength in patients with lateral epicondylitis.…”
Section: Discussionmentioning
confidence: 99%